Recovery of Posterior Communicating Artery Aneurysm-Induced Oculomotor Palsy after Coiling - Hanse, M.C.J.; Gerrits, M.C.F.; van Rooij, W.J.; Houben, M.P.W.A.; Nijssen, P.C.G.; Sluzewski, M. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Recovery of oculomotor (cranial nerve [CN] III) palsy after surgery of posterior communicating artery (PcomA) aneurysms has been well documented, but recovery after coiling is poorly understood. In this study, we report the recovery after coiling of PcomA aneurysm-induced CN III palsy in 21 patients at follow-up of 1 to 7 years.MATERIALS AND METHODS: Of 135 patients with a PcomA aneurysm treated with coils between January 1997 and December 2003, there were 21 patients with initial CN III dysfunction who were selected and reevaluated. There were 2 men and 19 women with a mean age of 54.9 years. In 17 patients, CN III palsy was associated with subarachnoid hemorrhage (SAH). Timing of treatment after onset of symptoms was 1 to 3 days in 5 patients, 4 to 14 days in 13, and more than 14 days in 3. Mean size of the aneurysm was 9 mm. Initial CN III palsy was complete in 15 patients and partial in 6. Mean follow-up after coiling was 3.7 years (range, 1–7 years).RESULTS: Of 15 patients with initial complete CN III palsy, recovery was complete in 3 and partial in 10. In 2 patients, complete CN III palsy was unchanged. Of 6 patients with initial partial CN III palsy, recovery was complete in 5 and partial in 1. Initial partial CN III palsy was the only predictor of complete recovery at follow-up.CONCLUSION: PcomA aneurysm-induced CN III palsy improves or cures after coiling in most patients. Complete recovery is more likely with initial partial dysfunction of the nerve.